Value added as the tax base for enterprise income - Nicos Zafiris (The Journal of Entrepreneurial Finance (JEF), 2016)
The paper addresses the long standing asymmetry in the tax treatment of debt and equity costs through a direct comparison of two hypothetical regimes based exclusively on income taxation, broadly defined, and value added taxation. The model presented widens existing debate to encompass the choice between entrepreneurial and contractual use of inputs generally and including labour, as well as capital. Using representative functional forms and numerical illustrations the analysis explores the effect of the tax regimes on firm decisions concerning input selection, output level and vertical integration. The greater neutrality of value added taxation is shown to produce gains in terms of firm efficiency in production and concentration on competitive advantage.
Keywords: H21; H25; H32; 650; residual income; income tax; value added tax; tax shield; neutrality; vertical integration